2014
DOI: 10.1124/dmd.113.053793
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-Dependent Inhibition of Paclitaxel Hydroxylation by Kinase Inhibitors and Assessment of Drug–Drug Interaction Potentials

Abstract: Paclitaxel is often used in combination with small molecule kinase inhibitors to enhance antitumor efficacy against various malignancies. Because paclitaxel is metabolized by CYP2C8 and CYP3A4, the possibility of drug-drug interactions mediated by enzyme inhibition may exist between the combining agents. In the present study, a total of 12 kinase inhibitors were evaluated for inhibitory potency in human liver microsomes by monitoring the formation of CYP2C8 and CYP3A4 metabolites simultaneously. For reversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 57 publications
4
53
1
Order By: Relevance
“…Apparent K I and k inact values for CYP2C8 inactivation by bosutinib were estimated to 54.8 mM and 0.018 1/min. Our findings differ from those of a recent study, in which bosutinib did not exhibit time-dependent inhibitory effects on paclitaxel 6a-hydroxylation, another CYP2C8 marker reaction (Wang et al, 2014). In addition, in this recent study, the inhibition of paclitaxel p-39-hydroxylation, which was used as a probe for CYP3A4 activity, increased following preincubation with NADPH as compared with no preincubation.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Apparent K I and k inact values for CYP2C8 inactivation by bosutinib were estimated to 54.8 mM and 0.018 1/min. Our findings differ from those of a recent study, in which bosutinib did not exhibit time-dependent inhibitory effects on paclitaxel 6a-hydroxylation, another CYP2C8 marker reaction (Wang et al, 2014). In addition, in this recent study, the inhibition of paclitaxel p-39-hydroxylation, which was used as a probe for CYP3A4 activity, increased following preincubation with NADPH as compared with no preincubation.…”
Section: Discussioncontrasting
confidence: 56%
“…The bosutinib results of the recent study correspond well with the inhibitory characteristics of bosutinib isomer 1 in our study. It should also be noted that this recent study observed weak mechanism-based inhibition of CYP3A4 by axitinib (Wang et al, 2014). In our study, detailed timedependent inhibition studies were not carried out with axitinib, because preincubation reduced its IC 50 CYP3A inhibition by less than 1.5-fold, which is a common criterion for time-dependent inhibition studies (Grimm et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The monitored ion transitions and collision energy (CE) were as follows: m/z 493.2 (M-H) / 317.3 and À25 V for steviol acyl glucuronide, m/z 0.453.3 (MþH) / 230.3 and 33 V for repaglinide, and m/z 469.5 (MþH) / 246.3 and 33 V for 3 0 -hydroxy repaglinide, respectively. The LC-MS/MS quantitation method of 6a-hydroxypaclitaxel was previously described (Wang et al, 2014b). Data were collected and processed using the AB Sciex Analyst 1.5.2 data collection and integration software.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…This topic has been reviewed, with excellent articles by Duckett and Cameron, [11] Stepan et al [13] and Teo et al [14] Reactive metabolites have been identified for the following clinically available tyrosine kinase inhibitors: dasitinib [15], gefitinib [16]. erlotinib [17], lapatinib [18,19], imatinib [20], axitinib [21], ponatinib [22], sunitinib [23], as well as investigational tyrosine kinase inhibitors. The purpose of the present review is to (1) provide updates on recently characterized bioactivation mechanisms of selected tyrosine kinase inhibitors, (2) discuss progress towards elucidating the cellular mechanisms of hepatocellular injury related to tyrosine kinase inhibitors, and (3) briefly discuss recent findings related to risk factors of tyrosine kinase inhibitor-induced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%